Stability-constrained two-stage robust optimization for integrated hydrogen hybrid energy system - Li, Qi (2021)
In order to cope with the challenges brought by multiple uncertainties to integrated hydrogen hybrid energy systems, a stability-constrained two-stage robust optimization method considering small disturbance stability and characteristics of dynamic response is proposed in this paper. In the first operating stage, the charging/discharging state of the battery and the start-stop state of the electrolyzer and fuel cell are determined. Then, power constraints for stabilizing ESSs power output is considered between the first and second stage optimization to improve the small disturbance stability of the robust operation plan. Then, the goal of minimizing the operation cost and determine a robust operation operating plan under the worst case is conducting in the second stage optimization. Through the small-signal model with time-delay effect, the eigenvalue analysis method is used to find the ESSs power range, and the small-signal stability of obtained robust operation plan can be enhanced. Finally, the effectiveness and superiority of the proposed method are proved by comparing with the traditional static robust optimization method. Impacts of uncertain parameters on economy and stability are also investigated in a typical example.